2019
DOI: 10.1097/prs.0000000000006282
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Revision Labiaplasty and Clitoroplasty after Gender-Affirming Genital Surgery

Abstract: Background: Penile inversion vaginoplasty is the most common gender-affirming procedure for transfeminine patients. Patients undergoing this procedure may require revision labiaplasty and clitoroplasty. This study describes complications and outcomes from the largest reported cohort in the United States to undergo penile inversion vaginoplasty with subsequent revision labiaplasty and/or clitoroplasty. Methods: A retrospective chart review was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 41 publications
2
52
0
2
Order By: Relevance
“…[31][32][33][34][35][36][39][40][41][46][47][48][49][52][53][54][55][56] Studies reported between 46.9% and 100% of patients able to be aroused postoperatively (median 85.7%). [31][32][33]35,51,64,65,67,68 Kerckhof et al (2019) found that a significantly lower percentage of patients (15.9%) had difficulties with sexual arousal postoperatively when compared with preoperative patients while controlling for hormone treatment. 42 Only one study qualified sexual arousal and reported that 75% of patients were satisfied with their arousal postoperatively.…”
Section: Arousalmentioning
confidence: 98%
See 2 more Smart Citations
“…[31][32][33][34][35][36][39][40][41][46][47][48][49][52][53][54][55][56] Studies reported between 46.9% and 100% of patients able to be aroused postoperatively (median 85.7%). [31][32][33]35,51,64,65,67,68 Kerckhof et al (2019) found that a significantly lower percentage of patients (15.9%) had difficulties with sexual arousal postoperatively when compared with preoperative patients while controlling for hormone treatment. 42 Only one study qualified sexual arousal and reported that 75% of patients were satisfied with their arousal postoperatively.…”
Section: Arousalmentioning
confidence: 98%
“…Most studies demonstrated that a high fraction of patients became more sexually active and satisfied with sexual activity following vaginoplasty when compared to pre-operativ ely. 45,64,65,68,102,107,121,124,153,156,159 In aggregate, 37-93.9% (median 75%) of 650 patients reported improvements post-operatively in satisfaction or happiness with their sex lives. 45,64,65,68,107,116,121,124,153,156 Bruck (2013) showed that prior to vaginoplasty less than 1 out of 10 women reported being satisfied with sexual activity, while postoperatively 3 out of 4 women were satisfied with their sexual activity.…”
Section: Self-lubrication/secretionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissatisfaction, even to the point of surgical regret, appears to be increased by the presence of surgical complications (2). Therefore, it is crucial to address potential future self-limited and non-self-limited complications, and communicate effectively how those complications will be ameliorated should they occur (15). Requests for revision, usually to improve features of the cosmetic appearance can include reconstruction of the clitoral hood, formation of a more defined labia minora, or reduction of labia majora size/bulk (5).…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Viruses, including Zika virus, Ebola virus, cytomegalovirus and human immunodeficiency virus (HIV), have been isolated from semen and can be sexually transmitted. 6,11,12 Furthermore, some viruses (eg HIV, Zika virus, herpes simplex virus (HSV) and human papillomavirus) can adhere to or be internalized by spermatozoa, 7,13 which may pose a risk for embryonic infection and cause adverse reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%